Characterization of a Novel Periodontal Ligament-specific Periostin Isoform. (September 2014) - Yamada, S.; Tauchi, T.; Awata, T.; Maeda, K.; Kajikawa, T.; Yanagita, M.; Murakami, S.
Periostin is a mesenchymal cell marker predominantly expressed in collagen-rich fibrous connective tissues, including heart valves, tendons, perichondrium, periosteum, and periodontal ligament (PDL). Knockdown of periostin expression in mice results in early-onset periodontitis and failure of cardiac healing after acute myocardial infarction, suggesting that periostin is essential for connective tissue homeostasis and regeneration. However, its role(s) in periodontal tissues has not yet been fully defined. In this study, we describe a novel human isoform of periostin (PDL-POSTN). Isoform-specific analysis by reverse-transcription polymerase chain-reaction (RT-PCR) revealed that PDL-POSTN was predominantly expressed in the PDL, with much lower expression in other tissues and organs. A PDL cell line transfected with PDL-POSTN showed enhanced alkaline phosphatase (ALPase) activity and calcified nodule formation, compared with cells transfected with the full-length periostin isoform. A neutralizing antibody against integrin-αv inhibited both ALPase activity and calcified nodule formation in cells transfected with PDL-POSTN . Furthermore, co-immunoprecipitation assays revealed that PDL-POSTN bound to integrin αvβ3 more strongly than the common isoform of periostin, resulting in strong activation of the integrin αvβ3-focal adhesion kinase (FAK) signaling pathway. These results suggest that PDL-POSTN positively regulates cytodifferentiation and mineralization in PDL cells through integrin αvβ3.